Chikungunya virus vaccines: Current strategies and prospects for developing plant-made vaccines. Issue 31 (17th July 2015) - Salazar-González, Jorge A.; Angulo, Carlos; Rosales-Mendoza, Sergio
Highlights CHIKV is a pathogen found in Africa, Indian Ocean Islands, Asia, and the Americas. No licensed vaccines against CHIKV are available. An overview on the developments of CHIKV vaccines is provided. The possible avenues to develop plant-made vaccines are analyzed.